2016
DOI: 10.1007/s12350-015-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-NaF PET/CT imaging in cardiac amyloidosis

Abstract: Cardiac amyloidosis (CA) is recognized as a common cause of restrictive cardiomyopathy and heart failure due to the deposition of insoluble proteins in the myocardial interstitium. We emphasize the role of [18F]-sodium fluoride (NaF) PET/CT as a potential noninvasive tool to identify and differentiate the transthyretin-related cardiac amyloidosis from the light-chain cardiac amyloidosis. We report cases of a 73-year-old man and a 75-year-old woman followed in our center for congestive heart failure with marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…As a potential PET substitute for bisphosphonate-based tracers, general feasibility of amyloid imaging using [ 18 F]NaF has been described in single case series whereas another report failed to identify increased tracer uptake in ATTR patients [125127]. Further studies are needed to further investigate the potential value of [ 18 F]NaF PET in CA.…”
Section: Cardiac Amyloidosismentioning
confidence: 99%
“…As a potential PET substitute for bisphosphonate-based tracers, general feasibility of amyloid imaging using [ 18 F]NaF has been described in single case series whereas another report failed to identify increased tracer uptake in ATTR patients [125127]. Further studies are needed to further investigate the potential value of [ 18 F]NaF PET in CA.…”
Section: Cardiac Amyloidosismentioning
confidence: 99%
“…Recent reports using PET imaging have demonstrated promise in subtyping CA [6668]. In a case study using (18)F- NaF, also a bone seeking tracer, diffuse myocardial enhancement was observed in a patient with ATTRm (Val122Ile) with no uptake in a patent with AL [66].…”
Section: Subtypingmentioning
confidence: 99%
“…In one pilot study, the use of 18F-NaF PET/CT was evaluated to differentiate AL from ATTR CA and reported positive myocardial uptake in a patient with Val122Ile TTR mutation and no uptake in the AL patient [57]. Subsequently, one study evaluated a patient with wild-type TTR and another with Ile68Leu TTR mutation and found no myocardial uptake in either [58].…”
Section: Introductionmentioning
confidence: 99%